Formulation and Evaluation of Buccal Mucoadhesive Bilayer Tablets of Apixaban - Juveria , Ayesha; Mannan , Abdul (Journal of Drug Delivery and Therapeutics, 2025)
Background: Apixaban is a factor Xa inhibitor, an anticoagulant; that exhibits low oral bioavailability (around 50%) as a result of its extensive first-pass metabolism, which highlights the need for improved delivery methods.Aim: This research is carried out to formulate and evaluate a bilayered buccal tablet formulation of Apixaban that adheres to mucosal surfaces.Materials and Methods: Apixaban was obtained from (NATCO Pharma Limited-Chemical Division, Hyderabad); The specified qualities were achieved in formulations (F1 to F9) by varying the amounts of polymers such as sodium alginate, hydroxypropyl methylcellulose (HPMC K4M), and Carbopol (934p). To make mucoadhesive bilayered buccal tablets, the direct compression method was employed. Tablets were evaluated for physicochemical properties (thickness, weight, hardness, drug content), mucoadhesive strength, in vitro drug release, and stability. Fourier-Transform Infrared (FTIR) spectroscopy assessed drug-excipient compatibility.Results: The optimized formulation (F7), with its 20 mg of Carbopol, was emerged from a series of testing. Excellent drug uniformity (approximately 99%), and strong adhesive properties. Drug release testing showed nearly 88% release within 180 minutes, following the first-order and Higuchi diffusion model (R² = 0.9904). FTIR confirmed no drug-excipient interactions, and stability studies at 40 °C / 75 % RH demonstrated physical and chemical integrity over three months.Conclusion: The formulated buccal mucoadhesive bilayer tablets provide a potentially effective, non-invasive route for apixaban administration that circumvents hepatic metabolism and enhance bioavailability.Keywords: Apixaban, Bilayered Buccal Tablet, Mucoadhesion, Direct compression method, Carbopol.